Different Storing and Processing Conditions of Human Lymphocytes do not Alter P-Glycoprotein Rhodamine 123 Efflux. - Gemma Chiva-Blanch; Pepita Giménez-Bonafe; Inés Llaudó; Joan Torras; Josep M Cruzado; Jordi Pétriz; Esther Castaño; Marcella Franquesa; Avelina Tortosa; Immaculada Herrero-Fresneda; Inés Rama; Oriol Bestard; et al. (Frontiers Media S.A., 2009)
P-glycoprotein (Pgp), a protein codified by Multi Drug Resistance (MDR1) gene, has a detoxifying function and might influence the toxicity and pharmacokinetics and pharmacodynamics of drugs. Sampling strategies to improve Pgp studies could be useful to optimize the sensitivity and the reproducibility of efflux assays. This study aimed to compare Pgp expression and efflux activity by measuring Rhodamine123 (Rh123) retention in lymphocytes stored under different conditions, in order to evaluate the potential utility of any of the storing conditions in Pgp functionality. Our results show no change in protein expression of Pgp by confocal studies and Western blotting, nor changes at the mRNA level (qRT-PCR). No differences in Rh123 efflux by Pgp activity assays were found between fresh and frozen lymphocytes after 24 hours of blood extraction, using either of the two Pgp specific inhibitors (VP and PSC833). Different working conditions in the 24 hours post blood extraction do not affect Rh123 efflux. These results allow standardization of Pgp activity measurement in different individuals with different timing of blood sampling and in different geographic areas.